How does economic development affect environmental health? - Bobur Toshbekov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The change of the environment to the negative side is closely related to economic development from the following three changes the higher level of pollution, global warming and the potential loss of environmental habitats, and the emergence of diseases.